Determinan Timeliness Penetapan Anggaran Pendapatan Dan Belanja Daerah Pemerintah Provinsi Di Indonesia - Marissa Ramdhany; Nurzi Sebrina; Mayar Afriyenti (Universitas Negeri Padang, 2019)
Timeliness of APBD is important in the management of provicianl finances. This research is aimed to examine the effect of government size, education background of executive, executive age, parliament size, parliament composition, liquidity, leverage, and auditor’s opinion as the determinants to timeliness of APBD in Indonesia. The samples used in this study are all local goverments in the provincial level for the year of 2016. This study used a binary logistic regression model to test the hypothesis. The results show that the local educational background of executive, parliament size, and parliament composition do not have significant influences on the timeliness of APBD, but only parliament composition and audit opinion of Indonesia Supreme Audit Board (BPK RI) have significant influences on the timeliness of APBD.